Isolation, Identification and Screening of the Yeast Flora from Indian Cashew Apple for Sugar and Ethanol Tolerance - Desai, Meghana V.; Dubey, Kavita V.; Vakil, Babu V.; Ranade, Vaijayanti V. (International Journal of Biotechnology for Wellness Industries, 2013)
Cashew apple juice is rich in fermentable sugars, minerals and vitamins, which makes it a suitable substrate for production of alcoholic beverages. In the present research work, indigenous flora of cashew apple (Indian variety) was studied. Seven morphologically different strains of Candida spp. were identified and checked for their sugar and ethanol tolerance. All seven isolates were able to tolerate sugar concentrations up to 25% but varied in their ethanol tolerance. Based on the above results it can be concluded that a high sugar and ethanol tolerant Candida spp. could be used as starter culture for commercial production of alcoholic beverages from cashew apple.